2021
DOI: 10.3390/ijerph18158111
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Health Behavior: Associated Factors in Surabaya High School Students, Indonesia

Abstract: (1) Background: The health behavior (HB) of adolescents develops in the school or family setting and plays an important role in their future health status. Health literacy (HL) has been identified as an important factor in modifying health behavior in addition to socioeconomic factors. health-promoting school (HPS) programs also have a significant role in providing students with the means of learning the importance of knowledge, behavior, and skills for a healthy lifestyle. (2) Method: This study aims to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
2
3
0
1
Order By: Relevance
“…In contrast, for FHL, which measures the ability to read, understand and calculate simple math in health information, a concerning outcome was obtained: only 164 (17.63%) students scored in the average category. The results on CHL and FHL in the undergraduate university students in Surabaya had a similar trend with the survey research we conducted on 1066 students in 15 high schools in Surabaya [ 65 ]. These commonly observed results of disparity between the CHL and FHL suggest the existence of a problem in health education and promotion at educational institutions that need to be addressed properly to improve the health outcomes and wellbeing of the students.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, for FHL, which measures the ability to read, understand and calculate simple math in health information, a concerning outcome was obtained: only 164 (17.63%) students scored in the average category. The results on CHL and FHL in the undergraduate university students in Surabaya had a similar trend with the survey research we conducted on 1066 students in 15 high schools in Surabaya [ 65 ]. These commonly observed results of disparity between the CHL and FHL suggest the existence of a problem in health education and promotion at educational institutions that need to be addressed properly to improve the health outcomes and wellbeing of the students.…”
Section: Discussionsupporting
confidence: 78%
“…This is in line with previous international studies on this subject. The authors of an Indonesian study led by Prihanto [ 50 ] achieved similar findings and identified an association between health behaviour and both HL level and socioeconomic factors among secondary school students in Surabaya, Indonesia. A cross-sectional study was conducted, with 1066 students evaluated as respondents.…”
Section: Discussionmentioning
confidence: 70%
“…Sejalan dengan pertimbangan yang diambil oleh tenaga pendidik lain (Yuliawati et al, 2021); (Prasada & Canon, 2021), tim penulis dan mahasiswa memilih lokus sekolah-sekolah yang ada di Desa Padaulun dengan pertimbangan pentingnya edukasi dan pendataan vaksinasi untuk anak-anak dan remaja usia 12-17 tahun. Literasi kesehatan pada masyarakat usia sekolah sangat penting untuk membentuk perilaku sehat di lingkungan masyarakat (Prihanto et al, 2021); (Yuliawati et al, 2021). Selain itu, persentase vaksinasi kedua untuk anak-anak dan remaja di Kabupaten Bandung belum mencapai 100%.…”
Section: Kataunclassified